Analisis Pengaruh Kualitas Layanan, Orientasi Pasar, dan Kepuasan Konsumen Terhadap Kinerja Pemasaran PT. Wisang Utama Mandiri Surabaya - Navi Muda Priyatna (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2015)
Abstract:Â Company competition surrounding today is colored with the fast changes and full of uncertainties. And, the problem faced by companies in present is the decrease of job volume, in which this matter takes place due to the impact of the decline of demands for the electric installation construction service to PT. Wisang Utama Mandiri. The job volume decline, perhaps, there any factors causing it, they are, among others, the poorly service quality, the market demands that not accommodated by the company, even the consumer satisfaction that not yet maximal, these cases, of course, so impacted on company incomes.From the result of testing on model in this research, by using random sampling, structural equation model (SEM) analysis, and the assistance of software Amos 22, on 100 respondents, that it was able to explain the Analysis of the Effects of Service Quality, Market Orientation, and Consumer Satisfaction on the Marketing Performance of PT. Wisang Utama Mandiri of Surabaya.The research result indicated that: 1) Service quality has effect on consumer satisfaction. 2) Service quality has effect marketing performace. 3) Market orientation has effect on consumer satisfaction. 4) Market orientation has effect on marketing performance. 5) Employee job satisfaction has significant effect on marketing performance.Of the three variables hypothesized as influential in this research, whose value largest is the direct relevance between market orientation and marketing performance.Key words:Â PT. Wisang Utama Mandiri, Service quality, Market orientation, Job satisfaction, Marketing performance